Work train hauling lumber for the construction of the White Pass & Yukon Railroad during the winter of 1898-1899, Alaska. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "White Pass and Yukon RR" Original image in Hegg Album 2, page 7.